NEURAL NETWORKS IN EDUCATION: AN INNOVATIVE APPROACH TO LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Today, in the era of globalization, digitization, the creation of new technologies, environmental problems and other serious changes that affect almost all aspects of human life and work and pose new challenges and tasks to humanity, education is a part of modern society. it was felt that it is the main condition for its development and survival. The rapid development of science, the expansion of the volume of knowledge and information creates a demand for the formation of new educational methods focused on the personal and social needs of a person during the production period. Currently, the development of new technologies and their practical use have become one of the main factors of increasing the competitiveness of any country. The term "artificial intelligence" has become widespread in our way of life, which is closely connected with today's technologies. Artificial intelligence is a system or technology capable of imitating human behavior in the performance of certain tasks, gradually improving itself using the acquired information. In general, artificial intelligence is neither a format nor a function, but a process that includes data collection, analysis, etc.